Responses to an ACT-based intervention according to binge eating severity in women (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Evidence indicates that binge eating correlates with weight related psychological symptoms and can interfere in successful weight management interventions. This study aimed to investigate the impact of a brief Acceptance and Commitment Therapy (ACT) based intervention according to binge eating severity in overweight and obese women, analyzing differences on weight related psychological symptoms and weight loss after the intervention. Participants (56) were recruited to take part on a 7-hour workshop intervention based on ACT and assessed at posttest and 3-month follow up. The outcomes were assessed using the following self –report measures: BES, AAQ-W, CFQ, BSQ, MEQ. Different symptom reduction profiles were identified according to binge eating severity. The group with severe symptoms had a larger effect size when compared to other groups. Binge eating symptoms severity seems to influence treatment response in a brief ACT based intervention. Future exploration of the underlying mechanisms of binge eating are warranted.
Keywords: binge eating; acceptance and commitment therapy; obesity; overweight; intervention